'Holy union?': The sectoral social partners and the Covid-19 crisis in Europe - Christophe Degryse (European Trade Union Institute (ETUI), 2021)
The economic and social crisis caused by the Covid-19 pandemic in Europe and around the world is without precedent since World War II if not before. With more than 40 million known cases in Europe in one year, and over 900 000 deaths (March 2020 to March 2021), governments have stepped up their emergency measures to contain the spread of the coronavirus: locking down their populations, closing non-essential businesses, closing offices, factories, schools and places of worship; cancelling cultural events, suspending sports contests and festivals; restricting people's movements, closing or monitoring borders, grounding airlines and more. Since March 2020, measures such as these have brought economic activity to a standstill. The interdependence of various economic sectors through supply chains, materials and transport for example, together with the fact that the shock hit supply and demand at the same time, mean that the crisis can be described as systemic. No sector has been spared: the entire economic system has taken a hit. The gross domestic product of the European Union shrank by 6.2% in 2020 (6.6% in the euro area), leading to soaring unemployment and temporary unemployment. The key question this paper attempts to answer is as follows: has European social dialogue played any useful part in this wholly exceptional economic and social situation?
Keywords: 330; social partners; industry development; coronavirus; impact analysis; EU countries; Sozialpartner; Branchenentwicklung; Coronavirus; Wirkungsanalyse; EU-Staaten